KEKUATAN HUKUM PENYELESAIAN TINDAK PIDANA KEKERASAN SESKUAL TERHADAP ANAK DI BAWAH UMUR SECARA ADAT - Halawa, Veronika (JURNAL PANAH KEADILAN, 2024)
Indonesia is a nation whose people have a diversity of ethnicities, races, religions and customs spread across cities and villages. In social life, law and society are two things that cannot be separated. Ubi societas ibi ius, where there is society, there is law, so a legal rule is needed to regulate social life in order to achieve public order. These rules are written or unwritten, apply nationally and regionally, in the field of public law and private law. The aim of the research is to find out and analyze the legal strength of resolving criminal acts of sexual violence against minors according to custom in Hilimaera Village, Ulunoyo Jenis District. The research used in this research is a type of sociological or empirical legal research (field research), namely examining applicable legal provisions based on existing facts in a society. Based on research findings and the results of interviews conducted by researchers in Hilimaera Village, Ulunoyo District, South Nias Regency, 30 days, starting from December 8 2023 to January 8 2024. In the resolution of cases of criminal sexual violence against minors according to custom in Hilimaera Village there were 2 (Two) cases that have been resolved. In the resolution of the two cases there was no difference, both cases were carried out through joint deliberation by traditional leaders, government, (village officials) by conducting negotiations on the problems that occurred. If it has been resolved by mutual agreement, in this case the perpetrator of a criminal act of sexual violence against a minor will be subject to customary sanctions, in the form of money amounting to Rp. 1,500,000 (one million five hundred) and one pig (bawi) five (alisi) in In this settlement, the victim also promised not to object to the perpetrator at a later time, referring to this, any community that violates the provisions of customary law, especially in Hilimaera village, will be subject to sanctions in accordance with applicable regulations.